2008
DOI: 10.5021/ad.2008.20.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-induced Linear IgA Bullous Dermatosis: A Case Report and Review of the Literature

Abstract: Linear IgA bullous dermatosis (LABD) is a rare autoimmune bullous disease that can either occur without any apparent cause or be induced by the administration of certain drugs, the most common of which is vancomycin. We present a case of a 45-year-old woman who was diagnosed with vancomycin-induced LABD by the presence of a characteristic linear band of IgA along the basement membrane zone on direct immunofluorescence microscopy. Our patient showed complete recovery after a 2-week period during which vancomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…Treatment is usually discontinuing the drug. Medications, including dapsone and high-potency topical steroids (such as clobetasol or betamethasone), are the first-line agents [4-7]. However, colchicine can be used if patients are unable to tolerate dapsone.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is usually discontinuing the drug. Medications, including dapsone and high-potency topical steroids (such as clobetasol or betamethasone), are the first-line agents [4-7]. However, colchicine can be used if patients are unable to tolerate dapsone.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is needed to ascertain the association between LABD, vancomycin, and heart disease [5, 7]. Lesions develop within 24 hours to 15 days after the first dose of vancomycin and new lesions usually cease to appear within one to three days after discontinuation of drug [1, 3, 8, 9]. Lesions vary in nature ranging from tense serous/hemorrhagic bulla (blister), string of pearl “herpetiform” configurations to targetoid/erythema multiforme-like eruptions.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphous clinical and immunopathologic features of this dermatosis can be partially explained by the different target antigens identified on Western blotting, including collagen type VII and the 97 kDa and 230 kDa antigens [2, 4, 5, 9, 12]. One study reported two cases of vancomycin-induced LABD with autoantibodies against BP180 and LAD 285 [5, 9, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vancomycin is regarded as one of the most common causes of drug‐induced LABD with perilesional biopsy specimens frequently demonstrating the characteristic linear IgA deposition on DIF . In the vast majority of these cases indirect immunofluorescence remains negative.…”
mentioning
confidence: 99%